PENGARUH PENGGUNAAN METODE PEMBELAJARAN SQ4R TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA SMP - Milah Rizki Amaliyah; Ediwarman; Sobri (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
Reading is an important skill that every individual needs regardless of age, gender, or educational level. Good reading skills enable individuals, especially students, to understand information more effectively. However, in reality, the reading skills of students in Indonesia tend to be low, partly due to the use of inappropriate learning methods. Based on these conditions, this study aims to examine the effect of the SQ4R and jigsaw strategies on the reading comprehension skills of seventh-grade students at SMPN 7 Pasar Kemis. The study used a quantitative quasi-experimental design with a non-equivalent control group and applied pretest-posttest pattern. The research sample consisted of seventh-grade students from classes VII E and VII F, who were selected using purposive sampling. Data were collected through an objective test consisting of 21 items and analyzed using statistical software. The results showed that the average posttest score in the class that applied the SQ4R strategy was 82.90, categorized as B “Good”, while the class that used the jigsaw strategy obtained an average score of 73.71, categorized as C “Fair”. These findings confirm that the SQ4R strategy has a more significant effect than the jigsaw strategy in improving the news text comprehension skills of seventh-grade students at SMPN 7 Pasar Kemis.